ROLE OF MEDIA IN RESILIENCE FROM FLOOD DISASTER: A CASE STUDY OF AUGUST 2008 KOSHI FLOOD IN NEPAL - Kafle, Kumud R.; Khanal, Sanjay N.; Dahal, Ranjan K. (Kathmandu University Journal of Science, Engineering and Technology, 2016)
A highly catastrophic river in the eastern part of Nepal - the Koshi (Sorrow of Bihar, India) - has been selected for this study. On 18th of August 2008, the river changed its original course towards the eastern side by breaking its embankment. Even though the flood was of great magnitude, surprisingly only the 2 casualties was reported because of prompt pre-information by media. The stratified random sampling from questionnaire shows that 77% respondents considered the radio (mostly FM radio) as the major source of information responsible for providing protection from flood as these warnings led people to take quick precautions. The survey showed that the timely forecast of disaster by FM radio and text message warnings were the most effective. The study also showed that the information flow at least 24 hours prior to the disaster would be manageable comfortably with community effort even without the presence of government rescue agencies. The role of other media such as newspapers and television are not as significant as radio and phone text messages. Kathmandu University Journal of Science, Engineering and Technology Vol. 12, No. 2, 2016, page: 83-87